Carbon Nanotubes: Optimizing Bifurcated Channels within an Anisotropic Scaffold for Engineering Vascularized Oriented Tissues (Adv. Healthcare Mater. 24/2020). Issue 24 (16th December 2020) - Fang, Yongcong; Ouyang, Liliang; Zhang, Ting; Wang, Chengjin; Lu, Bingchuan; Sun, Wei
Abstract : In article number 2000782 by Ting Zhang and co‐workers, a facile approach is developed to optimize bifurcated channels in anisotropic scaffolds. The bifurcated channel network governed by biomimetic principles is designed based on Murray's Law and further optimized by oxygen transport simulation and biological experiments. This numerical model–based strategy provides a practical guide to optimizing vascular channels for oriented tissue engineering.